2009
DOI: 10.1021/jm9003973
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Chemoenzymatic Synthesis, Cytotoxic Evaluation, and SAR of Epoxysterols

Abstract: A library of diastereomerically pure epoxysterols, prepared by combining chemical and enzymatic methodologies, was evaluated for cytotoxicity toward human cancer and noncancer cell lines. Unsaturated steroids were oxidized by magnesium bis(monoperoxyphthalate) hexahydrate in acetonitrile, and the resulting epimeric epoxides were enzymatically separated using Novozym 435 or lipase AY. Some of the synthesized epoxysterols have potent cytotoxicity and higher activity on cancer cell lines HT29 and LAMA-84.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 77 publications
6
35
0
Order By: Relevance
“…7b-hydroxycholesterol (7b-OHC) was provided by Mohammad Samadi (Metz, France) [45]; quality control was realized with 1 H and 13 C NMR spectra obtained with a Bruker Avance 400 spectrometer; the purity was >99% ( Supplementary Figure 1). Stock solutions of 7b-OHC were prepared in absolute ethanol at 800 mg/ mL (2 mM), sonicated for 10 min and stored at 4 C. Biotin (Sigma-Aldrich) stock solution was prepared at 0.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…7b-hydroxycholesterol (7b-OHC) was provided by Mohammad Samadi (Metz, France) [45]; quality control was realized with 1 H and 13 C NMR spectra obtained with a Bruker Avance 400 spectrometer; the purity was >99% ( Supplementary Figure 1). Stock solutions of 7b-OHC were prepared in absolute ethanol at 800 mg/ mL (2 mM), sonicated for 10 min and stored at 4 C. Biotin (Sigma-Aldrich) stock solution was prepared at 0.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…42,43 To a mixture of 36 (36.0 mg, 0.0677 mmol) and CeCl 3 Á7H 2 O (76.2 mg, 0.205 mmol) in THF (2 mL) and MeOH (1 mL) was added NaBH 4 (16.1 mg, 0.426 mmol) at 0°C. The mixture was stirred at ambient temperature for 14 h and then diluted with AcOEt.…”
Section: 238mentioning
confidence: 99%
“…The organic layer was washed (aqueous ammonium chloride, aqueous sodium bicarbonate, brine), dried (Na 2 SO 4 ), and concentrated. The resultant acetate(42) was used for the next reaction without further purification. A solution of the acetate and TBAF (1 M in THF, 2 mL, 2.00 mmol) in THF (20 mL) was stirred at ambient temperature overnight and then diluted with AcOEt.…”
mentioning
confidence: 99%
“…In the 1 H-and 13 C-NMR data of compounds 1 -4, there were large differences in the chemical shift values for skeletal positions C-3, C-5, C-6, C-7, and C-19 (Table 1). In particular, the 13 C-NMR chemical shift values  C 65.6 (C-5) and 62.6 (C-6) in 1, and  C 67.8 (C-5) and 61.3 (C-6) in 2 were attributed to those of an epoxide ring [4], suggesting that C-5 and C-6 of 1 and 2 were not connected to hydroxy groups. On the other hand, we reported 5,6-epoxy-(22E)-ergosta-8,22-diene-3,7-diol (5) and 5,6-epoxy-(22E)ergosta-8(14),22-diene-3,7-diol (6) from G. frondosa (Figure 1) [3].…”
mentioning
confidence: 96%
“…The novel 3,5,6,7-tetrahydroxylated structures of 1 and 2 were proposed on the basis of NMR data using COSY, HMQC and ROESY experiments [1]. During our studies on the sterol constituents from Japanese mushrooms [2], we reported the isolation and structure elucidation of two polyoxygenated sterols having the same A/B ring system as those of 1 and 2, (22E)-ergosta-8,22-diene-3,5,6,7tetraol (3) and (22E)-ergosta-8(14),22-diene-3,5,6,7-tetraol (4), from the edible mushroom Grifola frondosa (Figure 1) [3]. Comparison of the 1 H-and 13 C-NMR data of 1 and 2 for the A/B ring system with those of 3 and 4, respectively, indicated that the reported NMR data do not fit well with the proposed structures 1 and 2.…”
mentioning
confidence: 99%